THE CORRELATION BETWEEN IgM/IgG DENGUE SEROLOGICAL TEST AND THROMBOCYTE HEMATOCRIT COUNT ON DHF PEDIATRIC PATIENTS AT UNS HOSPITAL - Maulani, Utiya Nabila; Hanafi, Muchtar; Mashuri, Yusuf Ari; Kamenyangan Sari, Maria Galuh (Placentum: Jurnal Ilmiah Kesehatan dan Aplikasinya, 2023)
Background: Dengue hemorrhagic fever (DHF) is an infectious disease transmitted by the Aedes aegepty mosquito and mostly occurs during the rainy season. This disease can affect all age groups but the occurrence was quite high in children. Supporting examinations and complete blood counts are required to establish the diagnosis of DHF. This study aims to determine the correlation between the results of IgM/IgG dengue serological test and thrombocyte hematocrit count.Methods: This cross-sectional study was conducted in the UNS Hospital from November to December 2020 and obtained 134 samples that match the inclusion and exclusion criteria. Secondary data were obtained from the medical records of DHF child patients who met the criteria of inclusion and exclusion. Thrombocyte and hematocrit counts were analyzed using chi-square test and Fisher exact test.Result: This study showed no significant correlation between the serologic test of IgM/IgG dengue and thrombocyte with a value p = 0.451 (p>0.05). There was also no significant correlation between the serologic test of IgM/IgG dengue and hematocrit (p= 0156, p>0.05) on DHF pediatric patients at UNS Hospital.Conclusion: Thus the serologic test of IgM/IgG of dengue had no correlation with thrombocyte and hematocrit count on DHF pediatric patients at UNS Hospital.